Improving Micromeritic Properties of Ibuprofen: An Agglomeration Approach (Bangladesh Pharmaceutical Journal, 2017)
Ibuprofen is one of the common NSAIDs having poor water solubility, low dissolution, weak flow properties and reduced compressibility. These downsides of ibuprofen crystal upraise crucial challenges during development of a dosage form. The aim of this present work was to modify the physical form of ibuprofen by changing micromeritic properties. Seven different formulations of ibuprofen agglomerates such as F-1, F-2, F-3, F-4, F-5, F-6 and F-7 were prepared to convert the needle shaped ibuprofen crystals into agglomerates so that the desired micromeritic properties can be achieved. In this study, agglomerates of ibuprofen were prepared by Quasi emulsion solvent diffusion (QESD) method in association with two surfactants (sodium lauryl sulphateand Tween 80) at three different concentrations for each. The micromeritic properties of the prepared agglomerates were evaluated for bulk density, tapped density, Carrs index, Hausners ratio, angle of repose along with the release behavior of agglomerates. From dissolution study, it was observed that the release of drug was directly proportional to the surfactant concentration. Here, it was also revealed that there was no interaction among ibuprofen and other excipients as evident from DSC and FTIR studies.Bangladesh Pharmaceutical Journal 20(1): 90-98, 2017